2022
DOI: 10.26672/anatolianbryology.1061190
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Medicinal Uses of Mosses

Abstract: The use of plants by people has a history as old as the existence of humanity. From ancient times to the present, humanity has sought solutions to diseases by making use of plants in nature. Plants that were beneficial against diseases by trial and error in the old times were recognized, used, and passed on to future generations. This process, which has been going on for centuries between plants and humans, continues as an ethnobotanical science that has been accepted worldwide today and where great resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that secondary metabolites of the S. fallax species have a pronounced antimicrobial effect [56]. The mechanism of action of this moss on bacteria has not been fully studied, but it seems to be related to a substance contained in it called Sphagnol [57].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that secondary metabolites of the S. fallax species have a pronounced antimicrobial effect [56]. The mechanism of action of this moss on bacteria has not been fully studied, but it seems to be related to a substance contained in it called Sphagnol [57].…”
Section: Introductionmentioning
confidence: 99%
“…The ethnobotanical uses of bryophytes have been documented in various regions, including Africa, America, Europe, Poland, Argentina, Australia, New Zealand, Turkey, Japan, Taiwan, Pakistan, China, Nepal, and different parts of South, North, and Eastern India (Chandra et al, 2017;Drobnik & Stebel, 2021). Furthermore, bryophytes have been recognized for their potential pharmacological activity, with specific genera such as Sphagnum, Marchantia, and Polytrichum being commonly used in traditional medicine (Benek et al, 2022). The high levels of genetic variability in certain bryophyte species challenge the traditional view of these plants as genetically depauperate, highlighting their potential for further exploration in medicine and other fields (Wyatt et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The use of various species of Sphagnum in ethnomedicine has certainly contributed to the research mentioned above and expanded knowledge about the use of this group of plants. In traditional Chinese medicine, they are used in the treatment of skin diseases, acne, eye diseases and hemorrhoids [ 18 ], while traditional Korean medicine finds them effective in treating heart pain and strokes [ 9 , 12 ]. Various facts regarding the historical usage of the genus Sphagnum in medicine and ethnomedicine were collected and described by Drobnik and Stebel in their work [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial and absorption properties allowed the effective use of these plants as early as in the Mayan Civilization [ 20 ]. Since 1880, they have also been used in Europe as wound dressings and in the prevention of gas gangrene, in particular during World War I [ 7 , 18 , 19 , 21 , 22 ]. Recent studies on species of the genus Sphagnum revealed the UV-absorbing effect of extracts obtained from various species, such as S. magellanicum Brid.…”
Section: Introductionmentioning
confidence: 99%